Factors and Indicators of Creative Leadership of Learning Program Heads of Expansion Education Schools in Southern Border Provinces - อือตระกูล, ชนภรณ์; จรจิตรล, สุจิตรา; เดชพิชัย, วัน (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
This research uses mixed methods. The objectives of this study were to investigate and analyze factors and indicators concerning creative leadership of learning program heads of expansion education schools in the Southern border provinces. Phase 1 the determine the factors and indicators concerning creative leadership of the study dealt with review of related literature and in-depth interviews with seven knowledgeable and experienced individuals. Phase 2 Exploratory Factor Analysis (EFA) sample group, program heads of expansion education schools in the Southern border provinces. 200 people use a simple random Sampling. Sampling Without Replacement. The questionnaire consisted of 80 questionnaires with content validity, using CVI values ​​. The reliability index of .96. Cronbach's The reliability of the data was 950. By rotating the axis of an element. With Promax. Exploratory Factor Analysis (EFA) was performed and it was found that the factors and indicators concerning creative leadership of learning program heads of expansion education schools in the Southern border provinces consisted of 10 factors and 61 indicators: 6 indicators of adaptation; 5 indicators of transformational leadership; 5 indicators of emotional intelligence; 8 indicators of creating visions; 10 indicators of communication and putting visions into practice; 6 indicators of creativity; 6 indicators of thinking outside the box; 6 indicators of desire for success; 4 indicators of directions and goals; and 5 indicators of job satisfaction.